2019
DOI: 10.1136/jech-2018-211132
|View full text |Cite
|
Sign up to set email alerts
|

Long work hours of mothers and fathers are linked to increased risk for overweight and obesity among preschool children: longitudinal evidence from Germany

Abstract: BackgroundMost existing studies on maternal employment and childhood overweight/obesity are from the USA. They are predominantly cross-sectional and show a consistent linear association between the two. Less is known about the joint impact of fathers’ and mothers’ work hours on childhood overweight and obesity.ObjectivesTo examine the impact of maternal and paternal work hours on overweight/obesity among children aged 1–6 years in Germany using longitudinal data.MethodsChild body weight and height and their pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 26 publications
4
31
2
2
Order By: Relevance
“…These findings are generally consistent with US studies, which have reported that additional hours of maternal work increase the probability of childhood overweight/obesity (7,9,14). In an Australian sample, a larger magnitude of effect was observed among lower-income families (13) in contrast with results from Germany (12) and the United States (5,7-10), where larger effects were observed among higher-income families.…”
Section: Study Importancesupporting
confidence: 88%
See 3 more Smart Citations
“…These findings are generally consistent with US studies, which have reported that additional hours of maternal work increase the probability of childhood overweight/obesity (7,9,14). In an Australian sample, a larger magnitude of effect was observed among lower-income families (13) in contrast with results from Germany (12) and the United States (5,7-10), where larger effects were observed among higher-income families.…”
Section: Study Importancesupporting
confidence: 88%
“…Although our study suggests that change in maternal employment was related to BMI z score during infancy, we did not find an association between change in maternal employment and infant overweight in income-stratified models. Li and colleagues also reported a null association between maternal work hours and overweight among infants in a non-US sample (12). Yet our income-stratified results for overweight were in the same direction as the results for BMI z score.…”
Section: Original Articlesupporting
confidence: 69%
See 2 more Smart Citations
“…58 Parental smoking, especially that of the mother (during pregnancy and after birth) risks development of obesity and also presents mothers as a poor role model. 59 While its an established fact that mothers longer working hours is associated as a higher risk for child becoming overweight, recent study has also suggested that fathers working hours (55 hours/week) strengthened the effect of mothers, 60 both working parents decrease the potential time given to the children for health promoting activities. Breast feeding is directly related to obesity risk and a clear dose response effect has been identified for its duration.…”
mentioning
confidence: 99%